Local healthcare resources associated with unmet healthcare needs in South Korea: a spatial analysis - Sang Min Lee; Dong Woo Huh; Young Gyu Kwon (Geospatial Health)
Despite national initiatives to enhance healthcare accessibility, unmet healthcare needs in South Korea remain notably high, particularly in specific regions. This study investigated the factors contributing to geographical disparities in unmet healthcare needs by employing spatial regression models to examine the spatial interactions between healthcare resources and unmet needs. Utilizing data from the 2020 Community Health Survey and Statistics Korea for 216 local government entities, excluding remote areas to ensure data consistency, we identified significant spatial clusters of unmet healthcare needs. These clusters are primarily located in non-metropolitan regions facing transportation barriers and limited healthcare infrastructure. Spatial regression analysis revealed that general hospitals and clinics are significantly associated with reduced unmet healthcare needs underscoring their critical role in mitigating regional disparities. In contrast, hospitals (≥30 beds) and convalescent hospitals did not exhibit significant effects, likely owing to their focus on specialised inpatient and long-term care services, which do not directly address immediate outpatient needs. These findings advance the understanding of how healthcare resource distribution impacts unmet needs at a regional level in South Korea and highlight the necessity for allocating general hospitals and clinics strategically to promote health equity. Based on these results, we recommend evidence- based policy interventions that optimise existing healthcare resources and strategically deploy new facilities in underserved regions. These insights provide valuable guidance for policymakers to reduce geographical health disparities and enhance overall public health outcomes.